Household Smoke Exposure as Risk Factor of Low Birth Weight among Infants in Gianyar - Kadek Susiana Dwi Lestari; I Wayan Gede Artawan Eka Putra; I Nyoman Mangku Karmaya (Public Health and Preventive Medicine Archive, 2015)
Background and purpose: The Bali Provincial Health Department reported that in 2013, 24 per 1000 live births were underweight, with the regency of Gianyar ranked 4th the highest (31 per 1000 births). Data from Riskesdas 2010 indicated that 31.0% of individuals 15 years and over smoked, 68.1% of them reported smoking in the household. This study aimed to investigate the relationship between household smoke exposure, pregnant women and low birth weight (LBW) in Gianyar. Methods: This study was a case control where low birth weight as a case and birth with normal weight as a control. Study sample was 116, consisting of 58 cases and 58 controls. Dependent variables were low birth weight, independent variables were smoke exposure. Data was obtained by interviewing the mothers, and secondary data was collected from community health centre records. Data was analysed using bivariate and multivariate analysis. Results: Bivariate analysis indicated that OR of 6.370 (95%CI: 2.836- 14.309) for exposure to husbands smoke and an OR of household smoke exposure was 6.577 (95%CI: 2.894-14.948). Multivariate analysis indicated that adjusted OR of exposure to husbands smoke was 7.479 (95%CI: 2.058-27.175), adjusted OR exposure to household smoke was 9.002 (95%CI: 9.002-33.286), and adjusted OR combined exposure to smoke from both husband and household members was 9.333 (95%CI: 3.417-26.201). Conclusion: Household smoke exposure significantly increased risk of low birth weight among infants in the regency of Gianyar.